2015
DOI: 10.1097/tp.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide Induces T Cell Apoptosis and Prolongs Islet Allograft Survival in Mice

Abstract: Arsenic trioxide may prevent allograft rejection by inhibiting T-cell proliferation and inducing T-cell apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Traditional Chinese medicines are attracting attention because of their many medicinal herb resources. Among them, Tripterygium wilfordii , 11 arsenic trioxide (As 2 O 3 ) 12 and Radix Isatidis 13 possess anti‐inflammatory and immunosuppressive properties. In this study, we focused on DCAAA, a new compound derived from Radix Isatidis .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicines are attracting attention because of their many medicinal herb resources. Among them, Tripterygium wilfordii , 11 arsenic trioxide (As 2 O 3 ) 12 and Radix Isatidis 13 possess anti‐inflammatory and immunosuppressive properties. In this study, we focused on DCAAA, a new compound derived from Radix Isatidis .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, As 2 O 3 and leflunomide showed non‐toxicity under the dose used in this study. Gao et al also proved in a mouse islet allotransplant model that As 2 O 3 is non‐toxic . These results indicated that As 2 O 3 may be the best option for combination with leflunomide.…”
Section: Discussionmentioning
confidence: 92%
“…As 2 O 3 has been used in clinical therapy of leukemia patients, and the mechanisms involved have been unveiled, but current studies indicated that As 2 O 3 could suppress alloimmune rejection . However, the efficacy of As 2 O 3 in xenotransplantation remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In MRL/lpr mice, treatment with 5 mg/kg/day of ATO for 2 months inhibited autoreactive lymphocytes and blocked the progression of autoimmune diseases [19]. In mice allogeneic islet transplantation model, treatment with 1 mg/kg/day of ATO twice per day significantly prolonged the survival of islet allograft [22]. A recent study suggested that ATO (1 mg/kg/day) suppressed acute graft-versus-host disease in mice [20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that ATO suppressed acute graft-versus-host disease in mice [20]. Our previous work demonstrated that ATO attenuated acute rejection and prolonged graft survival in heart [21] and islet [22] transplantation models. These findings indicate that ATO elicits anti-inflammatory and immunosuppressive effects.…”
mentioning
confidence: 96%